Enhanced mechanical properties and electrical conductivity of Chitosan/Polyvinyl Alcohol electrospun nanofibers by incorporation of graphene nanoplatelets - Bazzi, Mohammadreza; Shabani, Iman; Mohandesi, Jamshid Aghazadeh (Journal of the mechanical behavior of biomedical materials, 2022)
The subject of this paper is to develop a highly conductive Graphene nanoplatelets (GNPs)-Chitosan (CS)/Polyvinyl Alcohol (PVA) (GNPs-CP) nanofibers with excellent mechanical properties. An experimental study was designed to produce nanofibers based on CP nanofibers as matrix and GNPs as reinforcement materials. The microstructure and the surface morphology of the electrospun nanofibers along with their electrical and mechanical properties were examined to study the effect of GNPs content. The SEM results showed that the gradual increase in GNPs content led to a porous web like morphology with no bead. There is a decrease in the diameter of nanofibers by increasing the concentration of GNPs to 1 wt% GNPs from 370 ± 40 nm for CP blend to 144 ± 18 nm for 1 wt% GNPs. Transmission electron microscopy results depicted that GNPs were dispersed uniformly confirmed by the absence of characteristic peak of graphite at 2θ = 26.5°. Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy results indicate the occurrence of a few interactions between GNPs and CP matrix. Nitrogen adsorption/desorption measurement demonstrated that increasing GNPs content increased the specific surface area of nanofibers from 238.377 to 386.708 m2/g for 0 and 1 wt% GNPs content. The test results also show that the presence of GNPs considerably enhances tensile strength, elastic modulus and electrical conductivity. Furthermore, the toughness of GNPs-CP nanofibers including 1 wt% GNPs significantly improved (12-fold) compared to the one for CP nanofibers. So, the proposed composite provides a decent functionality for nanofibers as scaffolds in tissue engineering applications.